Disorientation in hypermedia environments : mechanisms to support navigation - Dias, Paulo (1999)
The problem of navigation in hypertext is quite often associated with (dis)orientation. We begin this article by making a review of several mechanisms to support navigation after having done a brief presentation of the phenomena “getting lost in the hyperspace.” To simplify and clarify our explanation we have assembled the various proposals of support to navigation into the following: 1) solutions regarding the tools to support navigation, 2) solutions regarding interface and navigation metaphors, and 3) solutions regarding hardware and other approaches to deal with this problem. The analyses made of each mechanism to support navigation intend to offer different points of view about the pros and cons of their use.